Quality implementation leveraging collective efficacy to make "what works" actually work - Donohoo, Jenni; Katz, Steven (College teacher) (Corwin, 2020)
Harness the power of collective efficacy to achieve quality implementation! Designed to overcome a common barrier to successful implementation of school improvement efforts--entrenched belief systems--this book digs deeper into the power of collective efficacy. Teams with a strong sense of collective efficacy devise ways to make "what's supposed to work" actually work, and find ways to exercise control over challenges that surround them. In addition to the examples from both inside and outside of education, readers will find  • Ways to create environments that tap into mastery as the number one source of collective efficacy  • Methods to strengthen vicarious experiences through observational learning  • Examination of social persuasion and affective states as additional sources of collective efficacy Expanding on this critically-important topic, this book accentuates the importance of collective efficacy as the single most important driver of student achievement and the key to successful implementation. This book is the spark you might need to look at implementation in a completely new light. OBC other books by Corwin: Collective Efficacy 9781506356495 The Intelligent Responsive Leader 9781506333151
Includes bibliographical references and index
Keywords: Teacher effectiveness; School improvement programs; Team learning approach in education; Teaching teams; Academic achievement